Molecular species of some glycerophospholipid classes of soft coral \(Sinularia leptoclados\) collected in Nha Trang, Khanh Hoa - Dang , Thi Phuong Ly; Pham, Minh Quan; Dang, Thi Minh Tuyet; V. Ermolenko, Ekaterina; Pham, Quoc Long (Vietnam Journal of Marine Science and Technology, 2022)
In the soft coral Sinularia leptoclados, 30 molecular species belonged to 4 glycerophospholipid classes, including 8 ethanolamine glycerophospholipid (PE), 13 choline glycerophospholipid (PC), 3 serine glycerophospholipid (PS) and 6 inositol glycerophospholipid (PI) molecular species were identified. PE 18:1e/20:4, PC 18:0e/20:4, PS 18:0e/24:5 and PI 18:0/24:5 are the most abundant species with value of 69.94%, 45.57%, 68.55% and 68.18%, respectively. The PE, PC, and PS classes are reported to contain alkylacylphospholipid; meanwhile, a considerable level of diacylphospholipid is found in PI. A large portion of C20:4n polyunsaturated fatty acid was found in PE and PC; meanwhile, C16, C18, C22, and C24 fatty acids were reported at a minor level. The most dominant polyunsaturated fatty acid in PI and PS is tetracosapolyenoic C24. In the presence of fatty acids specific for the biosynthesis of zooxanthellae18:4n and 22:6n, PC is the most influenced class by the lipid composition of symbiotic microalgae. The PC 16:0e/18:4 and PC 18:1e/22:6 molecular species with recorded content of 1.69% and 8.05% are the evidence for lipid transportation from zooxanthellae to host corals. The PE, PS, and PI classes exhibit the lipid composition of the host coral; also, they are less affected by zooxanthellae lipids.